The image‐guided operating room—Utility and impact on surgeon's performance in the head and neck surgery. Issue 9 (9th July 2019) - Muhanna, Nidal; Douglas, Catriona M.; Daly, Michael J.; Chan, Harley H. L.; Weersink, Robert; Qiu, Jimmy; Townson, Jason; de Almeida, John R.; Goldstein, David; Gilbert, Ralph; Yu, Eugene; Kucharczyk, Walter; et al.
Abstract: Background: The image‐guided operating room (OR) is an emerging standard for dealing with complex cases in many surgical disciplines including neurosurgery, thoracic surgery, maxillofacial trauma, and orthopedic surgery. Its use in head and neck oncological surgery is not well established. The primary aim of this study was to assess the image quality of cone‐beam CT (CBCT) under real clinical conditions. The secondary aim was to assess the effect on surgical performance and decision making. Methods: Intraoperative 3D imaging was performed using a CBCT capable C‐Arm mounted on a multi‐axis robot (Siemens Zeego) in the image‐guided OR. All patients had immediate preoperative imaging taken with further intraoperative imaging performed as required. Ten initial patients, comprising 28 intraoperative scans, were used for questionnaire‐based image reviews conducted with experienced head and neck clinicians. Scans were assessed for aspects of both image quality and clinical utility, on separate 5‐point Likert scales (1‐5). Results: The median rating for bony detail was 4 out of 5. Vascular detail was increased ( P < 10 −8 ) from 1 to 3 with the use of IV contrast (region of interest CT# was 284 HU [SD, 47 HU]). Images were rated as 4 for freedom from artifact. Soft tissue definition was 2, with no significant improvement ( P = .2) with the addition of IV iodinated contrast. Surgeons rated the greatest clinical utility (4) for the CBCT when assessing postreconstruction imaging of a complex case. Conclusions: The image quality of CBCT in the image‐guided OR is good for bony detail and complex oncological reconstructions in the head and neck setting but probably has limited benefit for intraoperative soft tissue delineation. Future studies must also focus on clinical outcomes to help demonstrate the value of the image‐guided OR.